An Investigation of the Influence of MBTI Personality on College Students’ Procrastination - Hu, Yiqiu; Guo, Wuyuan (Transactions on Social Science, Education and Humanities Research, 2024)
Procrastination is the act of delaying essential tasks. It involves avoiding immediate action on a task by engaging in unrelated activities, leading to delays. Recognized as a detrimental habit, procrastination significantly impacts college students' lives. Prior research has primarily focused on physiological and environmental factors influencing procrastination. This study investigates the correlation between MBTI personality types and procrastination among college students. Data from 621 university students, collected through a questionnaire, were analyzed using SPSS. The findings indicate a tendency for individuals with NP-type personalities to procrastinate more, whereas those with J-type personalities are less inclined to do so. The complex relationship between personality and procrastination is highlighted, enhancing our understanding of its influence. This research provides valuable insights for both students and educators in addressing procrastination.